National and Subnational Incidence, Mortality, and Years of Life Lost Due to Breast Cancer in Iran: Trends and Age-Period-Cohort Analysis Since 1990 - Ataeinia, Bahar; Saeedi Moghaddam, Sahar; Shabani, Mahsima; Gohari, Kimiya; Sheidaei, Ali; Rezaei, Nazila; Naderimagham, Shohreh; Ghasemi, Erfan; Rouhifard Khalilabad, Mahtab; Roshani, Shahin; Farzi, Yosef; Farzadfar, Farshad (Frontiers in Oncology, 2021)
Breast cancer is the most common cancer among women, causing considerable burden and mortality. Demographic and lifestyle transitions in low and low-middle income countries have given rise to its increased incidence. The successful management of cancer relies on evidence-based policies taking into account national epidemiologic settings. We aimed to report the national and subnational trends of breast cancer incidence, mortality, years of life lost (YLL) and mortality to incidence ratio (MIR) since 1990. As part of the National and Subnational Burden of Diseases project, we estimated incidence, mortality and YLL of breast cancer by sex, age, province, and year using a two-stage spatio-temporal model, based on the primary dataset of national cancer and death registry. MIR was calculated as a quality of care indicator. Age-period-cohort analysis was used to distinguish the effects of these three collinear factors. A significant threefold increase in age-specific incidence at national and subnational levels along with a twofold extension of provincial disparity was observed. Although mortality has slightly decreased since 2000, a positive mortality annual percent change was detected in patients aged 25-34 years, leading to raised YLLs. A significant declining pattern of MIR and lower provincial MIR disparity was observed. We observed a secular increase of breast cancer incidence. Further evaluation of risk factors and developing national screening policies is recommended. A descending pattern of mortality, YLL and MIR at national and subnational levels reflects improved quality of care, even though mortality among younger age groups should be specifically addressed.